Unlearning established organizational routines – Part II. Issue 2 (6th February 2017) - Fiol, C. Marlena; O'Connor, Edward J.
Abstract : Purpose: The purpose of Part II of this two-part paper is to uncover important differences in the nature of the three unlearning subprocesses, which call for different leadership interventions to motivate people to move through them. Design/methodology/approach: The paper draws on research in behavioral medicine and psychology to demonstrate that initial destabilizing of old patterns and the subsequent behavioral processes of discarding the old and experimenting with the new are qualitatively different. Findings: Leadership interventions must fit the unique requirements of each unlearning subprocess. Discarding old routines requires continued focus on the costs of not doing so, as well as a progressive refocus on positive possibilities and engaging people in activities to explore them. When aspects of the old routine resurface, the costs of relapse must again become salient, leading to further discarding-from-use, followed by further positive experimentation. Finally, maintaining long-term release of an embedded routine requires recognition of the emerging new patterns and a shift from future-oriented visioning of possibilities to current satisfaction with the new. Originality/value: All empirical studies of organizational unlearning imply some form of destabilization of old learning as an antecedent to unlearning, and many of them discuss subsequent behavioral and cognitive displacement. However, they have not clearly distinguished between these subprocesses to fine-tune how to motivate people to move through them. This paper addresses that gap.